Impacts of drought and responses of rural populations in West Africa: a systematic review - (:unkn) unknown (My University, 2016)
In West Africa, climate variations and droughts have always affected livelihoods but have also triggered adaptation strategies. A better understanding of the impacts of drought and the responses of West African populations is indispensable for researchers and decision makers in the current and future context of multiple socioeconomic and environmental changes, including climate change. We conducted a systematic review of the literature on drought in West Africa. In this paper, we highlight controversial issues and identify knowledge gaps. Although drought has been widely considered as a major problem in West Africa, there is a need to frame it within a set of multiple threats faced by local populations and to understand how droughts act as a trigger in economic, societal, and environmental contexts. The literature on responses to drought focuses on agricultural and individual responses, while diversification, migration, and tree-based or livestock-based responses are less frequently addressed. More research is needed on the effectiveness and on the unexpected effects of responses of populations, states, and NGOs, as well as on the interactions between different responses. To understand the complexity of impacts and responses, the context in which they occur and how individual and collective actions interact within households or communities needs to be taken into account. Ecosystems and agriculture offer many goods and services that are suitable for adaptation and the different landscape components should be analyzed together. Such historical, contextual, and integrated analyses would better inform new policies and projects for adaptation to climate change.
Keywords: African Research